(untitled) (Bangladesh Journal of Agricultural Research, 2010)
Petiole of six genotypes of oilseed Brassica viz. Tori-7, Sampad, Kallyania, BARI Sarisha-7, BARI Sarisha-8, and MM 20-3 were cultured in MS medium with different concentrations of BAP, NAA, and AgNO3 for callus induction and subsequent plant regeneration. The highest percentage of callus induction (91.43%) was observed in Tori-7 in the media supplemented with 2 mg/L BAP, 0.1 mg/L NAA and 2.0 mg/L AgNO3. Calli were maintained in order to get sufficient number of regenerants. With the increased concentration of BAP, the highest percentage (57.14) of regenerants were found in Tori-7 followed by Sampad (33.13%) and BARI Sarisha-8 (31.42%) in MS media supplemented with 2.5 mg/L BAP, 0.1 mg/L NAA and 2.0 mg/L AgNO3. Root formation from the regenerants was found best in half MS medium supplemented with 0.5 mg/L NAA in genotype Tori-7. Regenerated plantlets of four genotypes (Tori-7, BARI Sarisha-8, Kallyania, BARI Sarisha-7) were successfully established in the field. Keywords: AgNO3; BAP; Brassica; NAA; regeneration. DOI: 10.3329/bjar.v35i2.5881 Bangladesh J. Agril. Res. 35(2) : 189-199, June 2010